Study on the morphological and metabolic changes of femur in laying hens with hypophosphatemia. (January 2021) - Yang, Naixi; Luo, Dongliu; Teng, Xiangqi; Liu, Zhihui; Wang, Haibin; Ge, Ming; Zhang, Ruili
Abstract: Layer fatigue syndrome caused by the lack of calcium and phosphorus can cause fracture in laying hens. The effect of phosphorus deficiency on the femur of laying hens with layer fatigue syndrome has not been studied. In this study, sixty 22-week-old Roman white layers were randomly divided into control group (group C) and low phosphorus group (group P), 30 individuals in each group. The available phosphorus content of group P was 0.18%. At the age of 26, 30 and 34 weeks, the production performance, biomechanical index, protein expression, histopathological change of femur and serological index were detected. The results showed that the laying rate, egg quality and body weight of laying hens, bone density, cortical bone thickness, rigidity, flexural modulus, flexural rigidity, the maximum load of femur and expression of osteocalcin (OCN), receptor activator of nuclear factor kappa-Β (RANK) and receptor activator of nuclear factor kappa-Β ligand (RANKL) decreased of group P. The number of osteocytes was decreased, and the voids was increased. However, cell lacunae were not obvious. The levels of phosphorus, calcium and OCN were increased, and the content of estradiol (E2 ), OPG and calcitonin (CT) were decreased in serum. In conclusion, the low phosphorus diet can induce layer fatigue syndrome and affect the content of OPG and E2 in serum and the expression of OCN, OPG, RANK and RANKL in femur protein, which leads to the imbalance of bone homeostasis, the thinning of femur cortex bone and the decrease of bone density. Highlights: Layer fatigue syndrome caused by low phosphorus diet. Pathological changes of femur in laying hens. The effect of layer fatigue syndrome on OPG / RANK signaling pathway.